1998
DOI: 10.1111/1467-7717.00097
|View full text |Cite
|
Sign up to set email alerts
|

Military Intervention and Humanitarian Action: Trends and Issues

Abstract: An important trend in military doctrine for so-called 'peace support operations' has been to place them on a spectrum that includes coercion and enforcement. This paper focuses on British writers of doctrine as those responsible for driving the debate forward and forging a consensus among leading military powers. Their discourse is combat oriented, a fact reinforced by a trend towards strategic subcontracting to coalitions of the militarily willing and able. At the same time, there has been a move to instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 6 publications
0
30
0
2
Order By: Relevance
“…First, it could not go beyond the negative consequences common in other areas of the moderated competition system, such as over‐reactions by donor provinces or cities and over‐competition among donor provinces or between cities (Gao, ). Such overreaction and over‐competition resulted in an imbalance between the ‘hard’ and ‘soft’ components of post‐disaster reconstruction projects (Pugh, ; Williams, , p. 268; Martz, ). Second, completing assigned tasks according to a tight schedule meant that there was a danger of donor provinces not understanding recipients’ demands, leading to disconnections between demand and supply, sometimes causing unnecessary wasteful investment.…”
Section: Resultsmentioning
confidence: 99%
“…First, it could not go beyond the negative consequences common in other areas of the moderated competition system, such as over‐reactions by donor provinces or cities and over‐competition among donor provinces or between cities (Gao, ). Such overreaction and over‐competition resulted in an imbalance between the ‘hard’ and ‘soft’ components of post‐disaster reconstruction projects (Pugh, ; Williams, , p. 268; Martz, ). Second, completing assigned tasks according to a tight schedule meant that there was a danger of donor provinces not understanding recipients’ demands, leading to disconnections between demand and supply, sometimes causing unnecessary wasteful investment.…”
Section: Resultsmentioning
confidence: 99%
“…When force is used, it is constrained by the time, place and precise combination 15. Pugh13 and Durch and Berkman16 argued that these operations have taken on only the veneer of classic consensual peacekeeping, while Seet and Burnham5 found that unintentional violence accounted for 41% of fatalities, followed by hostile acts (36%) and illness (21%). In terms of statistical probabilities comparing pre-Cold War UN PKOs with post-Cold War UN PKOs, the odds of UN PKO personnel dying from acts of violence increased by 50%, whereas the odds of fatalities due to unintentional acts decreased by 25% and those from illness remained constant or increased slightly.…”
Section: Resultsmentioning
confidence: 99%
“…These models aide in collective learning and fostering shared accountability and responsibility, especially in environments where the actors coming together may be coming from different frames of reference. In the given context, it is arguable that military "culture" is not easily reconciled with that of traditional development actors (see Pugh 1998). Several respondents highlighted differences in DND's culture with respect to CIDA and DFAIT, referring to this as an administrative challenge for civil -military coordination.…”
Section: Joint Decision-makingmentioning
confidence: 99%